What are the effects of taking 300 pills of sodium valproate? - case report - Kinga Pożarowska; Kinga Brzuszkiewicz; Gracjan Rudziński; Michał Tchórz (Kazimierz Wielki University, 2022)
INTRODUCTION: Sodium valproate is one of the most important antiepileptic drugs. It can be effective as a preventive treatment for migraine, it has also found use in the maintenance treatment of bipolar disorder and acute mania,it is sometimes used in the treatment of chronic neuropathic pain and fibromyalgia, in the treatment of schizophrenia borderline personality disorder and acquired brain injury, this drug is used off-label. Its overdose can be fatal. MATERIALS    AND  METHOD:  Patient  information  was  collected  from  hospital  records available in the clinical toxicology department. In addition, we conducted a literature review on sodium valproate treatment, its toxicity, side effects and pharmacokinetics using PubMed. CASE  REPORT:  A 57-year-old patient with a history of depressive disorders was admitted to the Clinical Department of Toxicology and Cardiology in Lublin for intentional intoxication with the drug Absenor (sodium valproate). The patient had taken 3 packages of Absenor 500 mg (300 tablets in total) for suicidal purposes. The determined concentration of valproic acid was 841 µg/ml, and the patient's condition was very severe. Despite the treatment administered-multiple attempts at gastric lavage, administration of activated charcoal, performance of hemodialysis procedures, administration of infusion of catecholamines, the patient died on the fifth day of hospitalization. CONCLUSION:  An overdose of sodium valproate can be fatal. Keep this in mind when ordering this drug for patients with a positive history of suicide attempts.